THE CAUSE FACTORS OF SPEAKING ANXIETY IN EFL CLASSROOM - Rahayu, Widya Adhariyanty (DINAMIKA DOTCOM, 2016)
This research investigated about the factors and situation causes the studentsâ anxiety inspeaking English as a Foreign Language (EFL) classroom. The data collected by quantitative andqualitative method. The quantitative data were collected by questionnaire through FLCAS. TheFLCAS consist of 5 point Likert scale. The data analyzed through Statistical Package for SocialSciences (SPSS) 20.0. Qualitative method was chosen through face to face interview to get indepth data or information about studentsâ speaking anxiety. The quantitative data presented thehighest reason of the students speaking anxiety is the studentsâ nervous and feel un-confidence inspeaking English. The qualitative data showed several factors and situations that create triggerand anxiety of students speaking such pronouncing the words, speak in front of class, speakingwithout preparation, and confused to create sentences. Keywords: Speaking Anxiety, English as a Foreign Language